THE PREVALENCE AND ASSOCIATED FACTORS OF BURNOUT SYNDROME IN INQUIRY OFFICIALS IN THE METROPOLITAN POLICE BUREAU - Ampornmunee, Nichapat (Journal of the Psychiatric Association of Thailand, 2021)
This research article aims to identify the prevalence and associated factors of burnout syndrome in police inquiry officials. A case control study was conducted among 338 police inquiry officials in the Bangkok Metropolitan Police Bureau. The participants were recruited and asked to complete a set of questionnaires, comprised of personal background, work experience, and the Thai version of Maslach Burnout Inventory (MBI) for burnout assessment. The researcher then performed a statistical analysis using Independent T-Test, One-Way ANOVA, and Multiple Logistic Regression to examine relevant factors contributing to the development of burnout syndrome in the sample group on three dimensions. According to research findings, it was found that most of the participants reported high scores on emotional exhaustion and depersonalization with low scores on reduced personal accomplishment, which are indicative of a high degree of burnout. Notably, the study indicated that over half of the samples were dissatisfied with their job (77.5 percent) and 88.2 percent of them used to have intent to leave the job. The main factors related to burnout syndrome development with a statistical significance included gender, underlying condition, economic status, and support from colleagues and supervisors. Therefore, this research recommended that the Royal Thai Police should improve compensation and welfare benefits for police inquiry officials along with the establishment of forums for knowledge and experience sharing among inquiry officials and their supervisors. These would help mitigate the development of burnout syndrome, enhance work effectiveness, and reduce police attrition rates.